Management of modern agricultural landscapes increases nest predation rates in Black‐tailed Godwits Limosa limosa. (2nd June 2015) - Kentie, Rosemarie; Both, Christiaan; Hooijmeijer, Jos C. E. W.; Piersma, Theunis
Abstract : Effective conservation of endangered species requires a solid understanding of the demographic causes of population change. Bird populations breeding on agricultural grasslands have declined because their preferred habitat of herb‐rich meadows has been replaced by grassland monocultures. The timing of agricultural activities in these monocultural grasslands is critical, as they often coincide with the nesting phase of breeding birds. Here, we aim to identify the effect of habitat management and targeted nest protection on nest survival of Black‐tailed Godwits Limosa limosa in the Netherlands, a population that has shown a 70% reduction in breeding population size since the 1970s. To protect nests in monocultures from destruction, farmers are paid to either delay mowing or leave a patch of unmown grass around the nest, a patch which in practice varied in size. In herb‐rich meadows, which are typically managed for bird conservation purposes, mowing occurs after hatching. Nest survival declined as the season advanced, more steeply on monocultures than on meadows. Targeted nest protection was only partially successful, as nest predation was considerably higher on mown grassland monocultures with small unmown patches around the nest than in mown monocultures with large unmown patches and in unmown fields. Increased predator densities over the years have been suggested as an important cause of the trend towards lower nest survival, but here we show that nest survival was higher on herb‐rich meadows than on monocultures, and similar to the 1980s. It thus seems that increased predator densities are an increased threat during the egg stage only if habitat quality is low. High‐quality habitat in the form of herb‐rich meadows therefore provides a degree of protection against predators.